Indian reserves, settlements and population centres in Québec - Surveys and Mapping Branch, Department of Mines and Technical Surveys (Producer) (Government of Canada, 1968)
Federal government map showing the locations of First Nations communities in Québec in 1968. The legend in the upper right corner shows different markings denoting, Indian Reserves, Indian Settlements, and Indian Population Centres. County and provincial boundaries are marked. Cities, towns, bodies of water, islands and other features are labelled throughout. Scale is 1:2,000,000. Reproduced from the 1:2,000,000 Map of Canada by the Surveys and Mapping Branch, Ottawa, 1968. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .